Mecanismo de ação preventivo da Spirulina platensis na hipercontratilidade induzida por ocitocina em útero de ratas Wistar com dismenorreia primária - Melchiades, Matheus Kelvin do Nascimento (2024)
Primary dysmenorrhea (DysP) is responsible for chronic pelvic pain that affects women and may be related to genetic, social and behavioral factors. The pharmacological treatment of this condition includes the use of non-steroidal anti-inflammatory drugs and antispasmodics; however, a significant number of women do not obtain a satisfactory response to these therapies. In previous studies, it was observed that DisP increased the contractile efficacy of oxytocin and supplementation with Spirulina platensis (SP) at a dose of 100 mg/kg prevented this increase in the uterus of Wistar rats. Therefore, it was decided to investigate the mechanism of action by which SP prevented the alterations in pharmacomechanical contractile reactivity induced by DisP in the uterus of rats. Data were expressed as mean and standard error of the mean, with significance level set at p < 0.05. The experimental procedures were approved by the Ethics Committee for Animal Use of UFPB - CEUA/UFPB (certificate 4080310124). Virgin Wistar rats were separated into the following groups: 1) control (GC); 2) rats with DysP (DisP), 3) rats with DysP and supplemented with SP 100 mg/kg (DisP + SP); and 4) rats with DysP that received the standard drug scopolamine + dipyrone (DisP + DP). The animals received, 24 hours before euthanasia, diethylstilbestrol (1 mg/kg, s.c.) for estrus induction. After euthanasia, the uterus was isolated, cleaned and suspended in organ baths under appropriate experimental conditions. Isometric contractions induced by oxytocin were monitored by isometric force transducers. Initially, cumulative concentration response curves to oxytocin were performed for the other groups. The results showed that animals in the DisP group presented greater contractile reactivity, while animals that received SP supplementation presented prevention of this uterine hypercontractility. Thus, the participation of the cyclooxygenase (COX), oxidative stress and nitric oxide (NO) pathways were evaluated. Based on the results obtained, it was observed that DisP increased uterine contractile efficacy due to increased activity of contractile prostanoids, decreased activity of superoxide dismutase and increased activity of the enzyme NADPH oxidase, in addition to favoring the reaction of NO with the superoxide anion forming peroxynitrite. Furthermore, these effects are prevented by SP supplementation, through inhibition of the COX pathway, decreased expression of reactive oxygen species (ROS), negative modulation of NADPH oxidase and negative modulation of nitric oxide synthase. These data show that in the uterus of rats there are changes in uterine contractility caused by DysP that are prevented by supplementation with SP, the mechanism of which is the decrease in contractile prostanoids, decrease in oxidative stress and decrease in peroxynitrite synthesis. Therefore, if these results are reproduced in women, S. platensis could be used as a dietary supplement to prevent oxidative damage and uterine contractile dysregulation in women with DysP.